Faktor-faktor Gaya Kepemimpinan yang Berhubungan dengan Motivasi Perawat Pelaksana Diruang Rawat Inap Rumah Sakit Pertamina Bintang Amin - Ni Wayan Oktavia Anjani; Usastiawaty C. A. S. Isnainy; Dewi Kusumanignsih (Universitas Malahayati Lampung, 2024)
ABSTRAK Decline in work motivation in health service workers has a negative impact on the quality of services provided by health workers, one of which is nurses. One of the factors that affect the low motivation of nurses is leadership, Leadership style is a method used in the leadership process, which is carried out through the leadership behavior of the head of the room to influence nurses to act according to the desire to achieve goals. The aim of this research is to determine the leadership style factors that are related to the work motivation of implementing nurses in the inpatient room at Pertamina Bintang Amin Hospital. Type of research used is quantitative where the design in this research uses an analytical survey with a cross sectional approach. The population in this study included nurses in pediatrics, surgery, internal medicine, 3rd floor and 4th floor, totaling 59 respondents. The sampling technique in this research is total sampling. Research shows that there is a relationship between democratic leadership style and work motivation. The result is a p-value of 0.001, where the p-value is 0.05, Odd-Ratio 37.500(7.219-194.796).There is a relationship between the democratic leadership style of the head of the room and the work motivation of implementing nurses at Pertamina Bintang Amin Hospital Keywords: Leadership Style, Democratic, Authoritarian, Participative, Motivational ABSTRAK Menurunnya motivasi kerja pada tenaga pelayanan kesehatan berdampak negatif terhadap kualitas pelayanan yang diberikan oleh tenaga kesehatan salah satu nya perawat. Salah satu faktor yang mempengaruhi rendahnya motivasi perawat adalah kepemimpinan, Gaya kepemimpinan adalah suatu cara yang digunakan dalam proses kepemimpinan, yang dilakukan melalui perilaku kepemimpinan kepala ruangan untuk mempengaruhi perawat agar bertindak sesuai dengan keinginan untuk mencapai tujuan. Tujuan penelitian ini adalah diketahui faktor-faktor gaya kepemiminan yang berhubungan dengan motivasi kerja perawat pelaksana di ruang rawat inap Rumah Sakit Pertamina Bintang Amin. Jenis penelitian yang digunakan adalah kuantitatif dimana rancangan dalam penelitian ini menggunakan survey analitik dengan pendekatan cross sectional. populasi dalam penelitian ini ada perawat pelaksana di ruang anak, bedah,penyakit dalam, lantai 3 dan lantai 4 yang berjumlah 59 responden. Teknik sampling dalam penelitian ini adalah total sampling. pada penelitian ini terdapat hubungan antara gaya kepemimpinan demokratis dengan motivasi kerja diperoleh hasil p-value 0,001 dimana nilai p-value 0,05 , dengan Odd-Ratio 37.500(7.219-194.796). Adanya hubungan antara gaya kepemimpinan demokratis kepala ruangan dengan motivasi kerja perawat pelaksana di Rumah Sakit Pertamina Bintang Amin. Kata Kunci: Gaya Kepemimpinan, Demokratis, Otoriter, Partisipatif, Motivasi